2000
DOI: 10.1046/j.1472-765x.2000.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Mitracarpus scaber extract and isolated constituents

Abstract: activity of a methanol extract and isolated constituents of Mitracarpus scaber, a species used in folk medicine by West African native people, was evaluated against Staphylococcus aureus and Candida albicans strains. The mitracarpus methanol extract possesses both antibacterial and antimycotic activities (minimum inhibitory concentration-MIC 31·25 and 62·50 mg ml −1 , respectively). This extract was subsequently fractioned and monitored by bioassays leading to the isolation of seven compounds screened for anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
3
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 8 publications
3
70
3
5
Order By: Relevance
“…O conjunto dessas informações espectrais permite indicar a substância S1 como o ácido 3,4,5-trimetoxibenzóico -ver estrutura na Figura 3. Em recentes pesquisas, essa substância apresentou atividade antimicrobiana, inibindo o crescimento de Staphylococus aureus (Besigmano et al, 2000).…”
Section: Resultados E Discussão Substâncias Químicas Isoladas E Identunclassified
“…O conjunto dessas informações espectrais permite indicar a substância S1 como o ácido 3,4,5-trimetoxibenzóico -ver estrutura na Figura 3. Em recentes pesquisas, essa substância apresentou atividade antimicrobiana, inibindo o crescimento de Staphylococus aureus (Besigmano et al, 2000).…”
Section: Resultados E Discussão Substâncias Químicas Isoladas E Identunclassified
“…Phytochemical evaluation revealed the presence of tannins which have been claimed to be responsible for its antimicrobial activity 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Mitracarpus villosus is a member of the family Rubiaceae. In various parts of tropical Africa, it is traditionally used for treatment of sore throat, ringworm and eczema, fresh cuts, wounds and ulcer (9,10,11). Previous studies also revealed that the plant contains biologically active substances such as fatty acids, flavonoids and other phenolic compounds with potential antifungal, antimicrobial and anti-inflammatory activities (12,13,14,15,16,17).…”
Section: Introductionmentioning
confidence: 99%